Five Non-motile Dinotom Dinoflagellates of the Genus Dinothrix - Yamada, Norico; Sakai, Hiroto; Onuma, Ryo; Kroth, Peter G.; Horiguchi, Takeo (Frontiers in Plant Science, 2020)
Dinothrix paradoxa and Gymnodinium quadrilobatum are benthic dinoflagellates possessing diatom-derived tertiary plastids, so-called dinotoms. Due to the lack of available genetic information, their phylogenetic relationships remain unknown. In this study, sequencing of 18S rDNA and the rbcL gene from temporary cultures isolated from natural samples revealed that they are close relatives of another dinotom, Galeidinium rugatum. The morphologies of these three dinotoms differ significantly from each other; however, they share a distinctive life cycle, in which the non-motile cells without flagella are their dominant phase. Cell division occurs in this non-motile phase, while swimming cells only appear for several hours after being released from each daughter cell. Furthermore, we succeeded in isolating and establishing two novel dinotom strains, HG180 and HG204, which show a similar life cycle and are phylogenetically closely related, to the aforementioned three species. The non-motile cells of strain HG180 are characterized by the possession of a hemispheroidal cell covered with numerous nodes, while those of the strain HG204 form aggregations consisting of spherical smooth-surface cells. Based on the similarity in life cycles, and phylogenetic closeness, we conclude that all five species should belong to a single genus, Dinothrix, the oldest genus within this clade. We transferred Ga. rugatum and Gy. quadrilobatum to Dinothrix, and described strains HG180 and HG204 as Dinothrix phymatodea sp. nov. and D. pseudoparadoxa sp. nov.